An atomistic approach to study the dynamic and structural response in 2D nanofiller reinforced polyethylene nanocomposites under ultra-short shock pulse loading. (June 2022) - Chaurasia, Ankur; Jalan, Salil Kanj; Parashar, Avinash
Abstract: An atomistic model was developed to systematically investigate the shock propagation and its attenuation behavior in two-dimensional (2D) nanofiller reinforced polyethylene (PE) nanocomposites. Under the framework of non-equilibrium molecular dynamics, an explicit ultra-short shock pulse with an impact velocity of 1.0 km/s was applied on the mono- and bi-crystalline 2D nanofiller reinforced PE nanocomposites. Their dynamic and structural responses were captured in terms of particle velocity, mean pressure, kinetic energy, and radial distribution function (RDF). The trends depicted that the energy dissipated from graphene (GNS) and boron nitride nanosheet (BNNS) reinforced PE nanocomposites were 30.69% and 24.92%, respectively, whereas the energy dissipation improves up to 45.33% and 41.77% for bi-crystalline GNS and bi-crystalline BNNS, respectively. Higher energy dissipation in GNS reinforced PE nanocomposites can be attributed to extreme impedance mismatch and superior interfacial interaction energy between GNS and PE chains. Highlights: Shock response of 2D nanofiller reinforced PE nanocomposites with the help of MD approach. Graphene is superior for attenuating shock in PE-based nanocomposites as compared to BNNS. Higher misorientation angle between nanosheets exhibits superior energy dissipation capabilities in PE nanocomposites.